Criminal Investigation Procedures in IT Crimes In accordance with UAE legislation - Al Mazrouei, Saeed Salem (Journal of Economic, Administrative and Legal Sciences, 2018)
This study dealt with the subject of the legal framework for the procedures of investigating the crimes of information technology in accordance with UAE legislation by reviewing the procedures of the police officers during the period of gathering the inferences and the preliminary investigation procedures conducted by the Public Prosecution to combat IT crimes. The legal problems and challenges facing the investigation of such crimes, and to determine the appropriateness of traditional criminal investigation methods in the field of information technology crimes. The study relied on the analytical description of the relevant laws and laws The study concluded with a series of results, the most prominent of which is that IT crimes require judicial officers to have a reasonable degree of culture in the field of IT systems so that they can initiate the procedures for collecting inferences, UAE Code of Criminal Procedure to the rules of control in the crimes of information technology is satisfied with the general rules for the control of crimes. The study also reached a number of recommendations, the most important of which is the need to subject the investigation bodies responsible for combating information crimes to specialized training that enables them to understand the contents of the communications related to the crimes of information technology and to assimilate crime scene data and to deal with the evidence obtained from the electronic means.